Influence of design parameters on the performance of a refractive index sensor based on SPR in plastic optical fibers - Al-Qazwini, Yusser A. Taqi; Muhammad Noor, Ahmad Shukri; Yaacob, Mohd Hanif; Mahdi, Mohd Adzir; Harun, Sulaiman Wadi (IEEE, 2015)
We report a refractive-index sensor based on surface plasmon resonance in etched plastic optical-fibers. Impact of fiber residual thickness and sensing length on the sensor's sensitivity is experimentally investigated.